Quantitative ethnobotanical study of medicinal plants used by native people of selected areas of Chhota Bhangal, Himachal Pradesh - Thakur, Anchal; Kumari, Ruchika; Kumar, Ashok; Chaudhary, Ashun (Ethnobotany Research and Applications, 2024)
Background: Ethnobotanical information about medicinal plants and their indigenous uses plays a major role in the conservation of biodiversity and cultural traditions. The native people of Chhota Bhangal hold the traditional knowledge and practices of using diverse medicinal plants for treating various diseases. But this traditional knowledge base is fading gradually. Keeping this in mind, the present study aimed to document the ethnobotanical data on medicinal plants traditionally used by the native people of Chhota Bhangal. Methods: Snowball sampling and a structured questionnaire were used to collect ethnobotanical data which was quantitatively analysed using Use Value, Relative Frequency of Citation, and Informant Consensus Factor. Results: A total of 66 plant species from 29 families were reported which are utilised traditionally by the residents of the study area. Different life forms of collected plants were herb (90.9%), trees (4.05%), climbers (3.03%), and shrub (1.5%). Asteraceae was the most utilised medicinal plant family (11 species) and leaves were the most utilised plant part (40%) for medicinal purposes. Picrorhiza kurroa was a highly used species with high UV and RFC values. ICF values range from 0.90-0.97 and the plant is used to cure gastrointestinal problems were highest in number. Conclusion: The study revealed that the native people of Chhota Bhangal still use several plants for curing different ailments and 66 plant species are reported with medicinal value. This documented ethnobotanical information will help in the conservation of ethnobotanical knowledge as well as further research for drug discovery to treat various chronic diseases. Keywords: Ethnobotany, Chhota Bhangal, Medicinal plants, IKS, Quantitative analysis